2021
DOI: 10.30871/jamn.v5i2.3770
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Usability Aplikasi Augmented Reality Procedure Mesin Wafer Mounting Di Teaching Factory Manufacture Of Electronics

Abstract: Augmented Reality adalah teknologi visualisasi yang saat ini cukup besar dikembangkan dalam berbagai bidang salah satunya dalam bidang pendidikan, namun di dunia pendidikan masih belum terlalu banyak digunakan. Teaching Factory Manufacturing of Electronics (TFME), saat ini masih menggunakan modul buku dan pembelajaran tatap muka sebagai sarana penyampaian materi khususnya di bidang pembelajaran mesin wafer mounting. Keterbatasan mesin yang digunakan secara bersamaan dengan minimal 5 mahasiswa, sehingga efektiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This research uses the same flow as previous research which starts from literature study, preparing scenario tasks, proceeds to the usability testing stage, analyzing data results, and finally conclusions [8], [9]. The flow of research shown in Figure 4.…”
Section: Methodsmentioning
confidence: 99%
“…This research uses the same flow as previous research which starts from literature study, preparing scenario tasks, proceeds to the usability testing stage, analyzing data results, and finally conclusions [8], [9]. The flow of research shown in Figure 4.…”
Section: Methodsmentioning
confidence: 99%